Pyridazinium-based ionic liquids as corrosion inhibitors for copper in phosphoric acid containing chloride: Electrochemical, surface and quantum chemical comparatives studies - Bousskri A.; Salghi R.; Anejjar A.; Jodeh S.; Quraishi M.A.; Larouj M.; Lgaz H.; Messali M.; Samhan S.; Zougagh M. (My University, 2025)
The acid corrosion inhibition and adsorption process of copper in 2M H3PO4 containing 0.3M of NaCl by an Ecofriendly ionic liquid newly synthesized [1-(2-(4-chlorophenyl)-2 oxoethyl)Pyridazinium Bromid CPEPB] and [1-(2-(4-nitrophenyl)-2-oxoethyl)Pyridazinium Bromide NPEPB]. Was studied by using weight loss measurements, electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization. The presence of these tow molecules led to decrease of the corrosion rate of Copper. At 10-3 M of NPEPB and CPEPB, the inhibition efficiencies increase with the inhibitor concentration to reach 88.94% and 87.5%, respectively. The adsorption of these compounds on Copper surface agrees Langmuir's adsorption isotherm. To support the experimental results and To perform the corrosion study, Quantum chemical approach, using the density functional theory (DFT), was applied in order to get better understanding about the relationship between the inhibition efficiency and molecular structure of NPEPB and CPEPB. The parameters include the lowest unoccupied molecular orbital (LUMO), highest occupied molecular orbital (HOMO), amount of electrons transferred and dipole moment. The results of the study suggest that NPEPB is a better corrosion inhibitor than CPEPB, which is in agreement with most experimental results obtained at different concentrations.